Left atrial dynamics and congestion status analysis in acute decompensated heart failure based on LVEF categorization. (14th October 2021) - Barki, M; Losito, M; Caracciolo, M M; Bandera, F; Rovida, M; Alfonzetti, E; Guazzi, M
Abstract: Background: Left atrial (LA) dynamics play a key role in the hemodynamics assessment of heart failure (HF). LA strain analysis by speckle tracking echocardiography (STE) has recently been introduced in clinical practice. In acute decompensated heart failure (ADHF), LA functional deterioration leads to worsening of pulmonary capillary hypertension and congestion, ultimately impacting prognosis. However, how LA size and function behaves in ADHF according to the different HF phenotypes has never been studied. Purpose: To evaluate the diverse morphology and dynamics of the LA, along with a thorough congestion analysis, in ADHF patients with HFpEF, HFmrEF and HFrEF. Methods: Eighty-five ADHF patients (mean age 75.6±10.4 years, 59% males) were prospectively enrolled within 24–48 hours from admission to the emergency department. In the acute phase all patients underwent a complete transthoracic echocardiography (TTE) and lung ultrasonography (LUS) associated with blood sample and a thorough clinical examination. LA mechanics was assessed with STE, through the evaluation of global peak atrial longitudinal strain (GPALS). Results: Out of 85 patients, 51% were classified as HFrEF, 20% as HFmrEF and 29% as HFpEF. At admission, all patients exhibited a comparable degree of congestion, as testified by increased IVC max. diameter (HFpEF 19±7 mm vs HFrEF 20±6.3 mm vs HFmrEF 17±5.3 mm, p=0.167), incremented PASP (HFpEF 39.2±13.5 mmHg vs HFrEF 42±12 mmHg vs HFmrEF 35.3±10.1 mmHg, p=0.15) and a rising number of B-lines on LUS (HFpEF 20±12.8 vs HFrEF 24±17 vs HFmrEF 21±19, p=0.62). Increased NT-proBNP values in the cohort were also noted, with HFrEF exhibiting the highest levels (HFrEF 11747±1069 ng/l vs HFmrEF 6905±811 ng/l vs HFpEF 3918±374 ng/l; p<0.001). When evaluating LA size and dynamics in the different HF phenotypes (HFrEF, HFmrEF and HFpEF respectively) a significant difference among the three subgroups was noted with HFrEF patients exhibiting a greater LA dilation and a higher impairment in terms of LA reservoir function (lowest GPALS/LAVi ratio) compared to HFpEF patients, who showed relatively less enlarged LA chambers and more preserved dynamics. Interestingly, HFmrEF patients expressed the best coupling between LA function and dimension, with significantly reduced LA dimensions and a more preserved LA function compared to HFrEF and HFpEF (LAVi: HFpEF 50.7±16 ml/m 2 vs HFrEF 53.9±15 ml/m 2 vs HFmrEF 42.8±10.8 ml/m 2, p=0.05*; GPALS HFpEF 17±9.1% vs HFrEF 10±4.85% vs HFmrEF 18.3±6.2%, p<0.001*) (Figure 1 and 2). Conclusions: ADHF patients exhibit an heterogeneous response in terms of LA size and function according to LVEF categorization. The definition of subjects expressing the worst coupling between LA size and function appears of relevance in order to facilitate risk stratification and identify patients at higher risk of early re-hospitalization. Funding Acknowledgement: Type of funding sources: None.